Is Dental Implantation Indicated in Patients with Oral Mucosal Diseases - Kalogirou Eleni-Marina; Sklavounou Alexandra (Balkan Stomatological Society, 2017)
Background/Aim: Dental implants are a reliable treatment choice for rehabilitation of healthy patients as well as subjects with several systemic conditions. Patients with oral mucosal diseases often exhibit oral mucosal fragility and dryness, erosions, blisters, ulcers or microstomia that complicate the use of removable dentures and emphasize the need for dental implants. The aim of the current study is to review the pertinent literature regarding the dental implantation prospects for patients with oral mucosal diseases. Material and Method: The English literature was searched through PubMed and Google Scholar electronic databases with key words: dental implants, oral mucosal diseases, oral lichen planus (OLP), epidermolysis bullosa (EB), Sjögren's syndrome (SS), cicatricial pemphigoid, bullous pemphigoid, pemphigus vulgaris, scleroderma/systemic sclerosis, lupus erythematosus, leukoplakia, oral potentially malignant disorders, oral premalignant lesions, oral cancer and oral squamous cell carcinoma (SCC). Results: Literature review revealed dental implantation in patients with OLP (14 articles), EB (11 articles), pemphigus vulgaris (1 article), SS (14 articles), systemic sclerosis (11 articles), systemic lupus erythematosus (3 articles) and oral SCC development associated with leukoplakia (5 articles). No articles regarding dental implants in patients with pemphigoid or leukoplakia without SCC development were identified. Most articles were case-reports, while only a few retrospective, prospective or observational studies were identified. Conclusions: Dental implants represent an acceptable treatment option with a high success rate in patients with chronic mucocutaneous and autoimmune diseases with oral manifestations, such as OLP, SS, EB and systemic sclerosis. Patients with oral possibly malignant disorders should be closely monitored to rule out the development of periimplant malignancy. Further studies with long follow-up, clinical and radiographic dental data are required to predict with accuracy the outcome of dental implants in patients with oral mucosal diseases.